1992
DOI: 10.1111/j.1751-0813.1992.tb09869.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovine nasal zygomycosis caused by Conidiobolus incongruus

Abstract: About 700 sheep died on 52 farms in north-western New South Wales and south-western Queensland over a 3 mo period. Affected animals had a marked asymmetrical swelling of the face, extending from the nostril to just anterior to the eyes. They lost condition rapidly and died within 7 to 10 days. At necropsy there was a unilateral severe necrogranulomatous rhinitis with extension of inflammation into the adjacent subcutaneous tissue, nasal septum and hard palate. Metastatic lesions were present in the draining ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
31

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 15 publications
1
49
0
31
Order By: Relevance
“…Desta forma ocorreriam 3 fatores importantes para o desenvolvimento do fungo: umidade; temperatura; e presença de matéria vegetal morta. Essa hipótese é sugerida, também, pela incidência significativamente maior da doença no primeiro semestre do ano, pois com as chuvas há maior crescimento do pasto, com maior quantidade de material decomposto, propiciando condições favorá-veis para o crescimento do fungo (Clark & Edington 1968, Carrigan et al 1992. De acordo com o relato dos produtores na primeira visita, 88% das criações apresentam a enfermidade no final das chuvas, entre os meses de abril e julho.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified
See 3 more Smart Citations
“…Desta forma ocorreriam 3 fatores importantes para o desenvolvimento do fungo: umidade; temperatura; e presença de matéria vegetal morta. Essa hipótese é sugerida, também, pela incidência significativamente maior da doença no primeiro semestre do ano, pois com as chuvas há maior crescimento do pasto, com maior quantidade de material decomposto, propiciando condições favorá-veis para o crescimento do fungo (Clark & Edington 1968, Carrigan et al 1992. De acordo com o relato dos produtores na primeira visita, 88% das criações apresentam a enfermidade no final das chuvas, entre os meses de abril e julho.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified
“…Nesse período a temperatura e a umidade relativa do ar são compatíveis com as exigidas para o crescimento de Conidiobolus spp. (King & Jong 1976, Segura et al 1981, Carrigan et al 1992, Ketterer et al 1992, Kwon-Chung & Bennett 1992.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified
See 2 more Smart Citations
“…However, this agent has medical importance (EL-SHABRAWI et al, 2014) and it was reported in ovine in Australia (KETTERER et al, 1992;CARRIGAN et al, 1992) and in dogs in United States of America (MACKEY et al, 2015).…”
Section: Clinical Manifestationsmentioning
confidence: 99%